The Relationship of Work Motivation and Creativity with The Performance of Science Teacher - Ade Sastrawijaya (Postgraduate, University of Mataram, 2023)
This study describes the relationship between work motivation and work creativity of science teachers both individually and simultaneously with the performance of science teachers at Kejaksan Elementary School, Cirebon City. This study aims to determine the strength of the relationship between work motivation and creativity with the performance of science teachers both individually and collectively. The research method used was a survey method with respondents coming from science teachers and school principals. The number of samples is 40 subjects, using proportional random sampling. The analysis used is parametric statistics using correlation and simple regression, and multiple regression, at a significance level of 0.05. The results of the hypothesis test shows: 1) there is a positive and significant relationship between work motivation and the performance of science teachers, indicated by the correlation coefficient ry1 = 0.37 and the regression equation Y = 108.3 + 0.191 X1, 2) there is a positive and significant relationship between teacher creativity and science teacher performance, indicated by the correlation coefficient ry2 = 0.30 and the regression equation Y = 83.0 + 0.3852 X2, 3) there is a positive and significant relationship between work motivation and teacher work creativity together with Science teacher performance is shown through the correlation coefficient ry1.2 = 0.54 and the regression equation Y = 59.05 + 0.16 X1 + 0.4X2. Based on these findings, the performance of science teachers must be improved systematically by the teachers themselves, the leaders, and the institutions that handle them.